Estimating the Health-Related Quality of Life Benefit of Prophylactic Treatment for COVID-19 in Immunocompromised People: A Multimethod Valuation Study - Katy Gallop; Rebekah Hall; Michael Watt; Daniel Squirrell; Neil Branscombe; Sofie Arnetop; Andrew Lloyd (Journal of Health Economics and Outcomes Research)
**Background:** Pre-exposure prophylaxis (PrEP) for COVID-19 provides additional protection, beyond vaccines alone, for individuals who are immunocompromised (IC). This may reduce the need for preventative behavioral modification, such as shielding—a behavioral restriction limiting an IC individual to minimize face-to-face interactions and/or crowded places. Therefore, PrEP may improve psychosocial well-being and health-related quality of life (HRQoL) for individuals with IC conditions.